COVID-19 vaccine delay: An examination of United States residents' intention to delay vaccine uptake - Carl Latkin; Lauren Dayton; Grace Yi; Afareen Jaleel; Chikaodinaka Nwosu; Rupali Limaye (Taylor & Francis Group, 2021)
The current study examines differences between COVID-19 vaccine intention and delay. A survey was administered to 585 US respondents in late November 2020 as part of an online longitudinal study. Respondents provided information on whether they would obtain a COVID-19 vaccine, once available, and how long they intended to wait before obtaining it. In the negative intention group, 3.4% reported waiting a few weeks, 34.0% waiting a few months, and 62.6% never getting vaccinated. In multivariable models, social norms were a significant and independent predictor of all vaccine delay and intention models. Vaccine delay was associated with low levels of worry about becoming infected with COVID-19, political conservatism, concerns about vaccine side effects, and low levels of believing a vaccine would be effective. Negative vaccine intentions were associated with worries about becoming infected with COVID-19, concerns about vaccine side effects, beliefs that the vaccines were developed too quickly, and low endorsement of the altruistic belief that older people should have vaccination priority. The study results highlight the importance of a multifactorial approach to assessing vaccine attitudes. The findings suggest that uptake programs should focus on enhancing pro-vaccine norms.